Role of transumbilical laparoendoscopic single-site surgery in the implementation ERAS in gynecology oncology: a retrospective study - Li, Fanlin; Zheng, Ying; Chen, Sijing; Wang, Qiao; Wang, Kana; Yang, Fan; Liu, Jianhong; Wang, Na (Frontiers in Oncology, 2025)
ObjectiveThe aim of the study was to verify the fast recovery effect of transumbilical laparoendoscopic single-site surgery by analyzing the operative and postoperative outcomes of patients with various gynecological malignancies in implementing The Enhanced Recovery After Surgery (ERAS) protocols.DesignA retrospective study.SettingA university academic hospital.Population or samplePatients with cervical, endometrial or ovarian cancer undergoing transumbilical laparoendoscopic single-site surgery by a single experienced surgeon.MethodsThis was a retrospective consecutive single-center study of patients with cervical, endometrial, or ovarian cancer undergoing transumbilical laparoendoscopic single-site surgery for full surgical staging from November 2017 to January 2022.Main outcome measuresThe main outcomes were the perioperative outcomes in various surgeries, including surgery time, estimated blood loss, length of hospital stay, and complications.Results315 gynecologic malignant cases successfully experienced transumbilical laparoendoscopic single-site surgery (TU-LESS) between November 2017 and January 2022 in West China Second Hospital were incorporated, including 195 cervical cancers, 85 endometrial cancers and 35 ovarian cancers. The average age for patients is 47.48 (SD = 8.77). 152 (48.25%) patients have a history of previous pelvic and abdominal surgery. The average operating time and blood loss are 273.71 (SD = 87.12) minutes and 166.87 (SD = 237.09) ml, respectively. The average time for the first passage of flatus is 43.68 (SD = 29.75) hours. The hospitalization is 5.30 (SD = 2.42) days on average.ConclusionsTU-LESS can enhance the recovery of patients who suffer from gynecological malignancies by implementing ERAS with fast flatus, less pain, shorter hospitalization and better rehabilitation.